2012
DOI: 10.1038/eye.2012.107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of simultaneous geographic atrophy and choroidal neovascularization

Abstract: Aim To investigate clinical presentation and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…22 23 In the present study, hypertension was not found to be linked to the prevalence of simultaneous GA and CNV. With regard to genetics, there was no association in the present study between the ARMS2 and CFH genes and the combined GA/CNV form of late AMD, a result which is concordant with the study by Grob et al, 25 which found no association between the combined GA/CNV phenotype of 20 patients and the following genes: high temperature requirement factor A1 (HTRA1), complement component 3 (C3), complement component 2 (C2), ARMS2, and CFH. However, Grob et al found that patients with the combined GA/CNV phenotype had a higher frequency of the ARMS2 and HTRA1 risk alleles compared to 154 patients with GA and 154 patients with CNV.…”
Section: Discussionsupporting
confidence: 93%
“…22 23 In the present study, hypertension was not found to be linked to the prevalence of simultaneous GA and CNV. With regard to genetics, there was no association in the present study between the ARMS2 and CFH genes and the combined GA/CNV form of late AMD, a result which is concordant with the study by Grob et al, 25 which found no association between the combined GA/CNV phenotype of 20 patients and the following genes: high temperature requirement factor A1 (HTRA1), complement component 3 (C3), complement component 2 (C2), ARMS2, and CFH. However, Grob et al found that patients with the combined GA/CNV phenotype had a higher frequency of the ARMS2 and HTRA1 risk alleles compared to 154 patients with GA and 154 patients with CNV.…”
Section: Discussionsupporting
confidence: 93%
“…However, as mentioned above, the evaluation of GA at study enrolment was based on colour fundus photography only and it is very likely that in some patients some atrophic areas were already present at baseline but not diagnosed due to haemorrhage or fibrosis. Grob et al ,39 investigated genotypes in patients with simultaneous GA and CNV in the same eye and compared them with patients with only GA or CNV. They found that none of the currently known at risk genotypes were significantly associated with occurrence of simultaneous GA and CNV.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that GA and CNV may be one disease on a continuum. It can therefore also be assumed that patients with GA will at some point potentially develop CNV and patients with CNV will at some point develop GA. GA associated with exudative AMD and pure GA may therefore be two phenotypes representing a single disease and have similar biochemical pathways 36 37 39…”
Section: Discussionmentioning
confidence: 99%
“…Most of the clinical studies, mentioned in their review article, focused on the incidence of CNV in eyes with GA at baseline as in the Macular Photocoagulation Study (MPS) and the Beaver Dam Eye Study. [23][24][25] In addition, Grob et al 26 found that GA tends to occur before CNV development in the combined form in their study, in which they found no significant higher frequency of certain gene alleles related to specific AMD phenotypes.…”
Section: Before the Anti-vegf Eramentioning
confidence: 99%